Effect of investment returns, risk-based capital, and underwriting results on the profit of Islamic life insurance company: A case study of PT. Takaful Keluarga 2017-2024 - Haerani, Sitti Annisa; Kholis, Nur (Journal of Islamic Economics Lariba, 2024)
IntroductionThe role of Islamic life insurance in addressing financial risks and promoting sustainable growth is increasingly important, particularly in Muslim-majority countries like Indonesia. Understanding the financial determinants of profitability in this sector provides critical insights into its operations and resilience.ObjectivesThis study examines the impact of investment returns, risk-based capital, and underwriting results on the profitability of PT Takaful Keluarga. It aims to evaluate both individual and combined effects of these financial variables and analyze their role during economic disruptions, such as the COVID-19 pandemic.MethodThe study employs a quantitative approach, utilizing multiple linear regression analysis on quarterly financial data from 2017 to 2024. The analysis focuses on the interplay of key financial variables and their influence on net profit, providing a comprehensive view of profitability determinants in Islamic life insurance.ResultsInvestment returns were found to significantly and positively affect profitability, highlighting the importance of effective asset management. Risk-based capital and underwriting results showed limited individual impacts but contributed significantly in combination with investment returns. The findings also underscore the company’s resilience, with profitability rebounding in the post-pandemic period.ImplicationsThe results emphasize the need for integrated financial strategies that align investment, solvency, and risk management practices. These findings offer actionable insights for practitioners and policymakers aiming to optimize the financial performance of Islamic life insurance providers.Originality/NoveltyThis study contributes to the understanding of financial dynamics in Islamic life insurance by addressing the interdependence of key financial variables and exploring their role in sustaining profitability under economic uncertainty.